Relationships Between Chemoreflex Responses, Sleep Quality, and Hematocrit in Andean Men and Women - Heinrich, Erica C.; Orr, Jeremy E.; Gilbertson, Dillon; Anza-Ramirez, Cecilia; DeYoung, Pamela N.; Djokic, Matea A.; Corante, Noemi; Vizcardo-Galindo, Gustavo; Macarlupu, Jose L.; Gaio, Eduardo; Powell, Frank L.; Malhotra, Atul; et al. (Frontiers in Physiology, 2020)
Andean highlanders are challenged by chronic hypoxia and many exhibit elevated hematocrit (Hct) and blunted ventilation compared to other high-altitude populations. While many Andeans develop Chronic Mountain Sickness (CMS) and excessive erythrocytosis, Hct varies markedly within Andean men and women and may be driven by individual differences in ventilatory control and/or sleep events which exacerbate hypoxemia. To test this hypothesis, we quantified relationships between resting ventilation and ventilatory chemoreflexes, sleep desaturation and breathing disturbance, and Hct in Andean men and women. Ventilatory measures were made in 109 individuals (n=63 men; n=46 women) and sleep measures in 45 of these participants (n=22 men; n=23 women). In both men and women, high Hct was associated with low daytime SpO2 (p < 0.001 and p < 0.002, respectively) and decreased sleep SpO2 (mean, nadir, and time <80%; all p < 0.02). In men, high Hct was also associated with increased end-tidal PCO2 (p < 0.009). While ventilatory responses to hypoxia and hypercapnia did not predict Hct, decreased hypoxic ventilatory responses were associated with lower daytime SpO2 in men (p < 0.01) and women (p < 0.009) and lower nadir sleep SpO2 in women (p < 0.02); decreased ventilatory responses to CO2 were associated with more time below 80% SpO2 during sleep in men (p < 0.05). The obstructive apnea index (OAI) and apnea-hypopnea index (AHI) also predicted Hct and CMS scores in men after accounting for age, BMI, and SpO2 during sleep. Finally, the heart rate response to hypoxia (HHR) was lower in men with higher hematocrit (p < 0.0001). These data support the idea that hypoventilation and decreased ventilatory sensitivity to hypoxia are associated with decreased day and nighttime SpO2 levels that may exacerbate the stimulus for erythropoiesis in Andean men and women. However, interventional and longitudinal studies are required to establish the causal relationships between these associations.